Pseudocapsule-Based Resection for Pituitary Adenomas via the Endoscopic Endonasal Approach - Zhou, Yuefei; Wei, Jialiang; Feng, Feng; Wang, Jianguo; Jia, Pengfei; Yang, Shuangwu; Gao, Dakuan (Frontiers in Oncology, 2022)
Introduction: The endoscopic endonasal approach (EEA) is a safe and effective treatment for pituitary adenomas (PAs). Since extracapsular resection(ER) of PAs improves tumor resection and endocrine remission rates, the interface between the pseudocapsule and gland draws increasing attention. However, it is difficult to precisely dissect the tumor along the exact boundary, and complete removal of the tumor increases the risks of normal tissue damage and cerebrospinal fluid (CSF) leakage. In this study, we investigated the extracapsular resection as well as the pseudocapsule histology to evaluate the effectiveness and safety of pseudocapsule-related surgical interventions. Methods: From December 2017 to December 2019, 189 patients of PAs via EEA in our single center were analyzed retrospectively. The images, operative details and clinical follow-up of patients were collected. Sixty-four patients underwent pseudocapsule-based ER and 125 patients also underwent traditional intracapsular resection (IR) with or without intensive excision for FPAs. The clinical characteristics, tumor resection, endocrinological outcomes, and postoperative morbidities of the two groups were compared. Informed consent for publication of our article was obtained from each patient. Histological examination of pseudocapsule was performed using hematoxylin and eosin and reticulin staining. Results: The gross total recession were 62 (96.9%) in ER group and 107 (85.6%) cases in IR group, whereas the endocrine remission rate was 29/31 (93.5%) and 40/53 (75.5%) cases respectively. Anterior pituitary functions were not aggravated postoperatively in any patient, but transient diabetes insipidus (DI) occurred more in IR group (64.0%) than in ER (48.4%). Pseudocapsules specimen were obtained in 93 patients, and clusters of small cells aggregation were detected in 11 pseudocapsule specimens(11.8%) whereas other patients showed no remarkable developed pseudocapsule. Intraoperative CSF leak occurred more in ER group (28.1%) than IR group (13.6%), but no difference was seen between two groups postoperative. No case of intracranial hematoma or pituitary crisis occurred in both groups. After a mean follow-up of 22.8 months, tumor recurrence was observed in 4 (2.1%) cases. Conclusion: Pseudocapsule-based extracapsular resection of PAs via EEA is an effective and safe procedure to achieve complete resection with high and sustained endocrine remission and without deteriorating pituitary function.